2020
DOI: 10.1177/1179547620972397
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Arrhythmia (Torsade de Pointes) in COVID-19: An Event Synergistically Induced by Viral Associated Cardiac Injury, Hyperinflammatory Response, and Treatment Drug?

Abstract: Arrhythmias in patients with coronavirus disease 2019 (COVID-19) are prevalent and deserve special attention because they are associated with an increased risk of fatal outcome. The mechanism of arrhythmia in COVID-19 remains unclear. Here, we report our first case of confirmed COVID-19 with documented Torsade de Pointes (TdP). A 64-year-old woman, previously healthy, presented to our emergency department with progressive shortness of breath, dry cough, and 1 week of fever. She was treated with chloroquine pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Another interesting point is the effect of SARS-CoV-2 on the cardiovascular system, as it may cause or conduce to acute cardiovascular events, microvascular thrombosis, myocardial damage, and arrhythmias [12,[66][67][68].…”
Section: Prognosis Of Covid-19 In Patients With Cardiovascular Risk Factors or Cvd-myocardial Injurymentioning
confidence: 99%
“…Another interesting point is the effect of SARS-CoV-2 on the cardiovascular system, as it may cause or conduce to acute cardiovascular events, microvascular thrombosis, myocardial damage, and arrhythmias [12,[66][67][68].…”
Section: Prognosis Of Covid-19 In Patients With Cardiovascular Risk Factors or Cvd-myocardial Injurymentioning
confidence: 99%
“…Recent studies have shown that COVID-19 is associated with acute myocardial involvement which described as an acute cardiac injury[ 3 , 12 , 13 ]. A suspicion of cardiac involvement in COVID-19 is best described by an elevation in cardiac biomarker [high-sensitivity troponin (hs-TnI)] above 99 th percentile upper reference limit[ 13 , 22 ]. Early reports had been analyzed, with notable findings suggest an increased level of cardiac troponin was associated with admission to intensive care and higher in hospital mortality[ 12 , 23 - 26 ].…”
Section: Heart Failure and Covid-19mentioning
confidence: 99%
“…Careful observation of the heart rate and rhythm are vitals in the clinical settings. Atrioventricular block, atrial fibrillation, polymorphic ventricular tachycardia and pulseless electrical activity have been closely associated with COVID-19 despite of the unknown mechanism of how these rhythms abnormalities may develop[ 22 , 35 ]. QT prolongation is constantly a thread, considering that QT prolongation is an independent risk factor of adverse outcome in advanced heart failure[ 36 ].…”
Section: Heart Failure and Covid-19mentioning
confidence: 99%
“…A lower pulmonary function is commonly found in HF patients and is contributed mainly by chronic obstructive pulmonary disease (COPD) [20]. Combination of underlying parenchymal disease and elevated left ventricular filling pressure leads to the development of pulmonary hypertension [21]. In COVID-19 infection, respiratory failure and acute respiratory distress syndrome (ARDS) further exacerbates pulmonary vasoconstriction and interstitial edema.…”
Section: Heart Failure and Covid-19mentioning
confidence: 99%